2003
DOI: 10.1016/s0895-7061(03)01013-6
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the type 2 dopamine receptor gene causes a sodium-dependent increase in blood pressure in mice

Abstract: These results suggest that D(2) receptors promote sodium excretion during a period of high salt intake. A defect in this mechanism may result in sodium-dependent BP elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 15 publications
0
36
0
1
Order By: Relevance
“…Hypertension was found in mice with deletion of both D 1 -like receptors (D 1 and D 5 ) (1, 31) and D 2 -like receptors (D 2 , D 3 , and D 4 ) (6,11,42). A multitude of cardiovascular, neurohumoral, and renal mechanisms may contribute to the phenotypes of these mice, but both D 1 -like and D 2 -like receptor deletions have been associated with sodium retention, extracellular fluid expansion, and salt-sensitive hypertension (1,6,42,54). The importance of the intrarenal autocrine/paracrine dopamine system in the natriuretic response to both acute and chronic sodium loading has also been demonstrated by pharmacological inhibition of the aromatic amino acid decarboxylase (8,53) and blockade of the renal dopamine receptors (28,29,39,47,49).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension was found in mice with deletion of both D 1 -like receptors (D 1 and D 5 ) (1, 31) and D 2 -like receptors (D 2 , D 3 , and D 4 ) (6,11,42). A multitude of cardiovascular, neurohumoral, and renal mechanisms may contribute to the phenotypes of these mice, but both D 1 -like and D 2 -like receptor deletions have been associated with sodium retention, extracellular fluid expansion, and salt-sensitive hypertension (1,6,42,54). The importance of the intrarenal autocrine/paracrine dopamine system in the natriuretic response to both acute and chronic sodium loading has also been demonstrated by pharmacological inhibition of the aromatic amino acid decarboxylase (8,53) and blockade of the renal dopamine receptors (28,29,39,47,49).…”
Section: Discussionmentioning
confidence: 99%
“…Those studies demonstrated that tyramine, octopamine, and dopamine can modulate chloride conductance in isolated Malpighian tubules. In mammals, it is well known that D2-like receptors are expressed in the kidney (Ricci et al, 2002;Nurnberger et al, 2004) where they modulate dopamine induced sodium excretion (Asico et al, 1998;Ueda et al, 2003). Taken together, these observations suggest that the fly may be utilized to investigate mechanisms underlying a range of D2 receptor-mediated physiogical processes.…”
Section: Figure 6 (Continued)mentioning
confidence: 99%
“…Depending on the genetic background [59,[79][80][81], knockout of all the dopamine-receptor gene subtypes in mice causes hypertension that can be aggravated by an increase in sodium chloride intake in D2 −/− , D3 −/− , D4 −/− , and D5 −/− mice; salt sensitivity of D1 −/− mice has not been tested.…”
Section: Genetic Evidence For the Role Of The D1 Receptor In Hypertenmentioning
confidence: 99%